PENERAPAN LAYANAN SOSIAL BERBASIS KELUARGA PADA LANSIA DI GRIYA BAHAGIA PMI SURAKARTA - Jihan Hasna' Ulfasari; Siany Indria Liestyasari; Sigit Pranawa (Universitas Hamzanwadi, 2021)
This study aims to determine the process of establishing family-based social services in Griya Bahagia PMI Surakarta and explain the form of implementation of family-based social services in Griya Bahagia seen from the performance of family functions in social services. This study uses the Social Construction Theory of Peter L. Berger and Thomas Luckmann, where the formation process of Griya Bahagia with a family-based social service system is inseparable from the social construction process, which includes the working mechanism of externalization, objectivation, and internalization that are dialectical. This research is a type of qualitative research with a phenomenological approach. The results of this study indicate that; (1) The purpose of establishing Griya Bahagia PMI is to humanize the neglected elderly like family. Therefore, to support the process of establishing family-based social services, Griya Bahagia then runs several program activities that aim to facilitate administrators in providing family-based social services to the elderly, (2) Several forms of implementing family-based social services at Griya Bahagia are manifested in various states of activities where each activity implements family functions in it.